Screening for latent infectious disease in patients with alopecia areata before initiating JAK inhibitors therapy: a single-center real-world retrospective study - Huang, Jundong; Tan, Zixin; Tang, Yan; Shi, Wei (Frontiers in Medicine, 2023)
Although there is growing evidence supporting the effectiveness of Janus kinase (JAK) inhibitors in treating alopecia areata, the high rate of recurrence following drug discontinuation has led to prolonged treatment courses and raised concerns about long-term safety. In clinical practice, caution should be exercised while using JAK inhibitors for various indications, and a comprehensive pre-treatment screening is recommended for each patient. This study presents an analysis of screening data collected from real-world settings before the initiation of Janus kinase inhibitors in patients with alopecia areata. Investigators collected retrospective medical data characterizing patients' screening data. Data on demographic and clinical data, including age, sex, disease duration, severity of alopecia tool scale , history of prior treatment, and treatment regimen were recorded. In this cohort (N=218), JAK inhibitors were initiated for 163 of 218 (74.8%) alopecia areata patients. The numbers of patients positive for antinuclear antibodies, hepatitis B surface antigen, hepatitis C virus antibodies, human immunodeficiency virus antibody, treponema pallidum hemagglutination assay, and thyroid-stimulating hormone were 32 (32/176), 10(10/218), 0 (0/218), 0 (0/218), 3 (3/218) and 9 (9/176), respectively. The number of patients with T-cell spot positive or imaging of the chest indicating tuberculosis was 37 (37/218). Our data provide additional information on the safety profile of JAK inhibitors in patients with alopecia areata. As such, it is necessary and crucial to screen for JAK inhibitors before it is used, particularly for individuals with a high risk of tuberculosis, hepatitis B, and other infections.